2016
DOI: 10.1021/acs.jproteome.6b00654
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Metabolic Profiling of the Tg197 Mouse Model Reveals Itaconic Acid as a Marker of Rheumatoid Arthritis

Abstract: Rheumatoid arthritis is a progressive, highly debilitating disease where early diagnosis, enabling rapid clinical intervention, would provide obvious benefits to patients, healthcare systems, and society. Novel biomarkers that enable noninvasive early diagnosis of the onset and progression of the disease provide one route to achieving this goal. Here a metabolic profiling method has been applied to investigate disease development in the Tg197 arthritis mouse model. Hind limb extract profiling demonstrated clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 51 publications
4
32
0
Order By: Relevance
“…The role of itaconate in RA is still debated. Despite evidence suggests an anti-inflammatory role (Mills et al, 2018) other studies have shown that reduced levels of itaconate correlate with a decreased pro-inflammatory (M1) signature in human macrophages isolated from healthy control subjects (Papathanassiu et al, 2017) and with a reduced arthritis severity in vivo (Michopoulos et al, 2016;Papathanassiu et al, 2017). It would be valuable to investigate how these observations in murine models translate into the human disease setting (i.e., OA vs. RA macrophages).…”
Section: Metabolites: a Focus On Lactatementioning
confidence: 99%
“…The role of itaconate in RA is still debated. Despite evidence suggests an anti-inflammatory role (Mills et al, 2018) other studies have shown that reduced levels of itaconate correlate with a decreased pro-inflammatory (M1) signature in human macrophages isolated from healthy control subjects (Papathanassiu et al, 2017) and with a reduced arthritis severity in vivo (Michopoulos et al, 2016;Papathanassiu et al, 2017). It would be valuable to investigate how these observations in murine models translate into the human disease setting (i.e., OA vs. RA macrophages).…”
Section: Metabolites: a Focus On Lactatementioning
confidence: 99%
“…Lactic acid enhances secretion of IL-6 and IL-23 from monocytes and macrophages [47]. Itaconate, a metabolic inhibitor of succinate dehydrogenase which has been shown to regulate succinate levels and secretion of inflammatory cytokines in activated macrophages [48], is also increased in the RA joint, and is associated with disease activity and response to therapy in animal models of arthritis [27]. Itaconate, a metabolic inhibitor of succinate dehydrogenase which has been shown to regulate succinate levels and secretion of inflammatory cytokines in activated macrophages [48], is also increased in the RA joint, and is associated with disease activity and response to therapy in animal models of arthritis [27].…”
Section: The Role Of Monocyte and Macrophage Metabolism In Ramentioning
confidence: 99%
“…Evidence for this metabolic switch in RA has been demonstrated by several studies showing an increase in mitochondrial dysfunction in the RA synovium [20], along with increased expression of glucose transporters (GLUTs) [21] and glycolytic enzymes, including hexokinase 2 (HK2), pyruvate kinase M2 (PKM2), glyceraldehyde 3-phosphate dehydrogenase (GAPDH), glucose-6-phosphate isomerase (GPI) and LDH [7,8,[21][22][23][24][25]. Marked accumulation of metabolic intermediates including lactate, glutamine, succinate [26] and itaconate [27] have been demonstrated in the RA joint which, in turn, can activate synovial cells Fig. 1.…”
Section: Review Series: Translating Immunometabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…K4IM cells were seeded at a density of 12,500 cells/cm 2 in 12‐well culture plates in 1‐ml 1:1 Dulbecco's Modified Eagle Medium/Nutrient Mixture F‐12 (DMEM/F12; HyClone Lab, Thermo Scientific, Logan, Utah, USA) supplemented with 1% penicillin/streptomycin and 10% FBS. The day after the medium was replaced with 1 ml of fresh serum‐free culture medium and K4IM cells were maintained for 24 hr with 10 ng/ml TNF‐α (Bio Basic Inc, Markham Ontario, Canada) as pro‐inflammatory stimulus (Michopoulos et al, ; Mrosewski et al, ). Unstimulated cells were used as control.…”
Section: Methodsmentioning
confidence: 99%